2011
DOI: 10.1055/s-0031-1273755
|View full text |Cite
|
Sign up to set email alerts
|

Urine Concentrations of Repetitive Doses of Inhaled Salbutamol

Abstract: We examined blood and urine concentrations of repetitive doses of inhaled salbutamol in relation to the existing cut-off value used in routine doping control. We compared the concentrations in asthmatics with regular use of beta2-agonists prior to study and healthy controls with no previous use of beta2-agonists. We enrolled 10 asthmatics and 10 controls in an open-label study in which subjects inhaled repetitive doses of 400 microgram salbutamol every second hour (total 1600 microgram), which is the permitted… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
21
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(23 citation statements)
references
References 20 publications
1
21
1
Order By: Relevance
“…A limitation of the present study was that the subjects were not elite athletes or asthmatics. Nonetheless, previous pharmacokinetic studies found no differences in the urine concentrations of salbutamol between athletic and non‐athletic subjects or between asthmatics and non‐asthmatics after oral and inhaled administration . Therefore, the present findings may be applicable for WADA.…”
Section: Discussionmentioning
confidence: 42%
See 1 more Smart Citation
“…A limitation of the present study was that the subjects were not elite athletes or asthmatics. Nonetheless, previous pharmacokinetic studies found no differences in the urine concentrations of salbutamol between athletic and non‐athletic subjects or between asthmatics and non‐asthmatics after oral and inhaled administration . Therefore, the present findings may be applicable for WADA.…”
Section: Discussionmentioning
confidence: 42%
“…While the administered dose of 1600 µg salbutamol as a single inhaled dose used in the present study, exceeds that considered as normal therapeutic treatment, athletes are often medically advised to inhale the amount that is needed to relieve asthma symptoms (pro re nata) . Athletes using salbutamol may inhale repetitive doses prior to a warm‐up and again before and after competition . Indeed, doping case reports have shown that athletes inhale salbutamol repetitively during competition .…”
Section: Discussionmentioning
confidence: 91%
“…Therefore, it seems unclear why urine samples of beta 2 ‐agonists are unadjusted for USG in doping analysis. Recent studies have reported urine concentrations of salbutamol near the decision limit of 1200 ng/mL when unadjusted for USG, even after inhalation of salbutamol in therapeutic doses within the current threshold . As such, Elers et al .…”
Section: Discussionmentioning
confidence: 99%
“…Using a triple quadrupole mass spectrometer, an LOQ of 24 ng/ml was accomplished and the fitness‐for‐purpose was shown by applying the established methodology to inter‐laboratory ring test samples. The rationale of the urinary threshold of 1000 ng/ml of salbutamol was re‐assessed by analyzing urine samples collected after repetitive dosing of inhaled salbutamol by asthmatic and non‐asthmatic persons up to the allowed daily amount of 1600 µg . After correction of measured urinary concentrations concerning their specific gravity, no sample exceeded the permitted threshold in either group, supporting the validity of the established limit.…”
Section: Beta‐2‐agonistsmentioning
confidence: 78%